A test bed for the experimental validation of position control algorithms - Akpolat, ZH; Asher, GM; Arellano-Padilla, J (Pergamon-Elsevier Science Ltd, 2004)
Controlled dynamometers are normally electrical machines used to provide a loading characteristic to prime mover drive trains, normally for the purpose of testing and validation. This paper describes a new dynamometer control strategy that can practically emulate the linear or non-linear dynamics of modelled mechanical loads. Since the real load dynamics are preserved, it is ideal for the experimental validation of robust or adaptive control strategies. Experimental results showing the effectiveness of the proposed dynamometer control approach are presented. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: dynamometer; electrical drives; control; test bed; induction machine